Highly Active and Robust Metalloporphyrin Catalysts for the Synthesis of Cyclic Carbonates from a Broad Range of Epoxides and Carbon Dioxide. Issue 19 (17th March 2016) - Maeda, Chihiro; Shimonishi, Junta; Miyazaki, Ray; Hasegawa, Jun‐ya; Ema, Tadashi
Abstract: Bifunctional metalloporphyrins with quaternary ammonium bromides (nucleophiles) at the meta, para, or ortho positions of meso ‐phenyl groups were synthesized as catalysts for the formation of cyclic carbonates from epoxides and carbon dioxide under solvent‐free conditions. The meta ‐substituted catalysts exhibited high catalytic performance, whereas the para ‐ and ortho ‐substituted catalysts showed moderate and low activity, respectively. DFT calculations revealed the origin of the advantage of the meta ‐substituted catalyst, which could use the flexible quaternary ammonium cation at the meta position to stabilize various anionic species generated during catalysis. A zinc(II) porphyrin with eight nucleophiles at the meta positions showed very high catalytic activity (turnover number (TON)=240 000 at 120 °C, turnover frequency (TOF)=31 500 h −1 at 170 °C) at an initial CO2 pressure of 1.7 MPa; catalyzed the reaction even at atmospheric CO2 pressure (balloon) at ambient temperature (20 °C); and was applicable to a broad range of substrates, including terminal and internal epoxides. Abstract : In a fix ! Bifunctional metalloporphyrins act as catalysts for the formation of cyclic carbonates from epoxides and CO2 (see scheme). A comparison of the catalytic activities shows the superior performance of meta ‐substituted catalysts. A robust zinc(II) porphyrin with eight nucleophiles at the meta positions shows the highest catalytic activity and a broad substrate scope, including terminal and internal epoxides.